Microhardness of fiberglass – reinforced photocomposite material under different conditions of light polimerization - Udod, Oleksandr; Roman, Oleh (ScienceRise: Medical Science, 2020)
The aim: to study in laboratory conditions the microhardness of a glass-fiber-reinforced photocomposite under different modes of light exposure at different times. Materials and methods. The microhardness of the everX Posterior, GC glass-fiber-reinforced photocomposite was investigated on 60 samples using a PMT-3 microhardness meter on three sample surfaces within 1 hour, 1 day and 7 days after polymerization. Samples of a cylindrical shape with a height of 3 mm of group 1 were irradiated with the light flux of a photopolymerizer in the "soft start" mode, samples of group 2 were polymerized with light of constant high intensity 1400 mW/cm2. Research results. After 1 hour, the microhardness on the surface closest to the LED was 87.34±1.21 kgf/mm2 in samples of group 1, 102.0±0.94 kgf/mm2 (p<0.05) in group 2, and 70.98±1.23 kgf/mm2 (the lowest indicator) and 90.65±1.12 kgf/mm2 (p<0.05). After 1 day, on the nearest surface, the microhardness increased in the samples of group 1 to 97.03±1.25 kgf/mm2, group 2 – to 114.61±1.13 kgf/mm2 (p<0.05), on the most distant - up to 75.95±1.11 kgf/mm2 and 99.83±1.24 kgf/mm2 (p<0.05), respectively. At 7 days, the indicators on the first surface in group 1 were 104.64±1.23 kgf/mm2, in 2 – 123.35±1.15 kgf/mm2 (p<0.05), on the other surface – 80.25±1.48 kgf/mm2 and 107.53±0.92 kgf/mm2 (p<0.05). The growth of microhardness on these surfaces for the entire period was 16.5 % and 11.6 % in the samples of group 1, and 17.3 % and 15.7 % in group 2. Conclusions. The light flux of constant high intensity provides statistically significantly (p <0.05) higher microhardness indices of the glass-fiber reinforced photocomposite on all surfaces of the samples than the light exposure in the “soft start” mode. In the direct restoration of teeth, it is necessary to reduce the thickness of the photocomposite layer for "soft start" polymerization